(untitled) (Eurasian Scientific Herald, 2022)
The on-board information system is an integral part of a modern car and serves to collect, process, store and display information about the driving mode and technical condition of the car, as well as external factors surrounding it. In the most developed countries, it is understood that the improvement of traffic on congested roads is possible only if the driver quickly orients himself in the traffic situation and traffic flows. This article describes the on-board information system of modern cars, its structure, design, sections and types.